As we celebrate, we indict: A personal reflection on 30 years of democracy by a rank-and-file activist - Mati, Shepi (New Agenda: South African Journal of Social and Economic Policy, 2024)
This is a personal reflection of a rank-and-file activist on 30 years of democracy in South Africa. Whilst it celebrates the achievements of democracy, it seeks to indict us all for the crime of ukuxhaphaza nokunyela abantu baseMzantsi Afrika, (abusing and trampling on the dignity of the people of South Africa). SHEPI MATI explores how the fight for democracy impacted on our emotions, our hearts and our experience of living under formal democracy. This year marks 30 years of democracy in South Africa. April 2024 was 360 months since all South Africans – irrespective of colour, class, gender or creed – cast their votes to choose their public representatives for the first time. If we were to count this in days, it amounts to 10,958 days. I still remember the excitement and the buzz in the long snaking queue to cast our votes on that historic Wednesday at the Salt River Town Hall in Cape Town. I seek to trace my own personal journey as a young person belonging to a generation who, in the words of Franz Fanon, took up the challenge to define their mission and sought to fulfil it.